Analisis Hubungan Waktu Pelayanan dan Faktor Total Quality Service Terhadap Kepuasan Pasien di Poliklinik Kebidanan dan Kandungan RSIA Anugerah Medical Centre Kota Metro Tahun 2015 - Mayasari, Fitriyuli (UI Scholars Hub, 2016)
Outpatient services is one of unit working in hospitals that serve patients with outpatient including all diagnostic and therapeutic procedures. The waiting time is one important thing that will determine the initial image of hospital services. One of the tools for identifying customer needs hospital is the Total Quality Service (TQS). Patient satisfaction is a major factor and a measure of the success of the hospital which is given to customers who impact the number of visits increased and patients are satisfied tend to be returned. This research is a quantitative research with cross sectional design (cross-sectional) with correlation analysis to analyze the relationship the dependent variable and independent variables. The study was conducted by calculating the waiting time and time clinic doctor examination, then conducted a TQS questionnaire survey on 135 respondents. The study states that the waiting time and the doctor’s examination time did not affect patient satisfaction. The quality of personnel, administrative services, medical care experiences, and social responsibility has a significant relationship with patient satisfaction. And the social responsibility factor is the most dominant variable and the effect on patient satisfaction.